2018
DOI: 10.5194/hess-22-5069-2018
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: An improved Grassberger–Procaccia algorithm for analysis of climate system complexity

Abstract: Understanding the complexity of natural systems, such as climate systems, is critical for various research and application purposes. A range of techniques have been developed to quantify system complexity, among which the Grassberger-Procaccia (G-P) algorithm has been used the most. However, the use of this method is still not adaptive and the choice of scaling regions relies heavily on subjective criteria. To this end, an improved G-P algorithm was proposed, which integrated the normal-based K-means clusterin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…However, the water level data and wave, noise, and rainfall-runoff components have stochastic characteristics as it showed a diverging pattern. Di et al (2018) confirmed that correlation dimension of rainfall data at a specific rainfall station is diverging even though the dimension increases [36]. Through the above study, we can estimate that the water level time series shows stochastic characteristics because the correlation dimension diverged without converging to a specific value.…”
Section: Estimation Of Correlation Dimensionsupporting
confidence: 58%
“…However, the water level data and wave, noise, and rainfall-runoff components have stochastic characteristics as it showed a diverging pattern. Di et al (2018) confirmed that correlation dimension of rainfall data at a specific rainfall station is diverging even though the dimension increases [36]. Through the above study, we can estimate that the water level time series shows stochastic characteristics because the correlation dimension diverged without converging to a specific value.…”
Section: Estimation Of Correlation Dimensionsupporting
confidence: 58%
“…Note that selection of scaling regions is critical for calculating CDs. The automated algorithm proposed by Di et al (2018) was utilized to select scaling regions. If D 2 (m) reaches a certain value (usually called a saturation value) after a value of m, the saturation value is defined as the CD of the time series X i (i = 1, 2, …, N).…”
Section: Correlation Dimensionmentioning
confidence: 99%
“…Conceptually, a chaotic system is controlled by few independent variables that are sensitive to initial conditions, which results in random‐looking processes (May, 1976; Sivakumar, 2004). Chaotic behaviors have been reported in rainfall (Di et al., 2018; Fuwape et al., 2017), streamflow (Ghorbani et al., 2018), and soil moisture (Di et al., 2019). Those studies suggested that the underlying systems regulating those hydrological processes are mainly controlled by few independent variables, the number of which is determined by the stochasticity of those processes; thus, it can provide useful information for various application purposes such as model parameterizations and hydrological simulation (Sivakumar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The calibration and verification of the SWAT model, using flow data collected at the An Khe hydrological station and the Cung Son hydrological station, was divided into two phases: calibration (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991) (Figure 6a,b) and verification (1992-2002) (Figure 6c,d). The parameter optimization techniques have been analyzed and applied in recent studies, such as Wang et al (2019) [83] and Di et al (2018) [84]. However, the automatic calibration process uses the SWAT Calibration Uncertainties Program (SWAT-CUP) software, with automatic algorithms that match the instability values.…”
Section: Calibration and Validation Of The Swat Modelmentioning
confidence: 99%